ANALISIS KREATIVITAS PESERTA DIDIK OLEH PENDIDIK DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN DI KELAS 4 DI SD NEGERI 064966 JALAN SEHATI - Yusniar Nainggolan; Suyit Ratno; Nenny Sipangkar; Mhd Irwansyah; Enny Daulay; Afni Tarigan; Lena Sagala; Nisa Rizkiyana (Cahaya Ilmu Bangsa Institute, 2024)
This research was motivated by completing the course assignment, namely creative development, so research was carried out on the creativity of grade 4 students at state elementary schools. 064966 on Jalan Be healthy. The research found problems including the existence of students who did not contribute enough to developing their creativity, a lack of material materials to develop students' creativity at the time and student involvement in the learning process is still lacking. The purpose of This research is to analyze the use of media for increasing the creativity of grade 4 students at Pleburan Elementary School 064966. This research is qualitative research. The technique used in data collection are observation and interviews. Subject in this research are grade 4 teachers and grade 4 students. Objects in research This is the use of learning media to increase the creativity of grade 4 students SD Negeri 064966. The results of the research show that media use learning supports the learning process, students are more interested and creative when participate in learning activities.